2020
DOI: 10.3390/agronomy10010129
|View full text |Cite
|
Sign up to set email alerts
|

Flaming, Glyphosate, Hot Foam and Nonanoic Acid for Weed Control: A Comparison

Abstract: Synthetic herbicides are commonly used in weed management, however, 70 years of use has led to weed resistance and environmental concerns. These problems have led scientists to consider alternative methods of weed management in order to reduce the inputs and impacts of synthetic herbicides. The aim of this experiment was to test the level of weed control using four weeding methods: glyphosate applied at an ultra-low volume, the organic herbicide nonanoic acid, flaming, and hot foam. The results showed that wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Those species were mainly represented by perennial rosette-forming weeds such as Rumex spp. and Plantago lanceolata L. Those findings confirm that thermal weeding techniques are not effective on these weeds' typology because of the resources stored in their roots [58]. Moreover, the summer weeds community exerts a higher pressure on eggplants, and this was aggravated by the sprinkler irrigation adopted.…”
Section: Weed Controlmentioning
confidence: 76%
“…Those species were mainly represented by perennial rosette-forming weeds such as Rumex spp. and Plantago lanceolata L. Those findings confirm that thermal weeding techniques are not effective on these weeds' typology because of the resources stored in their roots [58]. Moreover, the summer weeds community exerts a higher pressure on eggplants, and this was aggravated by the sprinkler irrigation adopted.…”
Section: Weed Controlmentioning
confidence: 76%
“…Plant cover was contained under tillage and flame weeding. Respect to mowing, the vegetation underwent a major disturbance which created a difficulty in re-sprouting [ 25 ]. Under mowing, instead, where many perennial and taller plants were detected, the plants were ready and adapted for a rapid regrowth (see also discussion about functional groups).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was shown that type and intensity of management can produce marked changes in the biodiversity associated to the vineyard [ 20 , 24 ]. As an example, concerning the merely weed control, flaming was compared to glyphosate, hot foam and nonanoic acid for weed control, and it was shown that flaming and hot foam were more efficient than the other tested techniques [ 25 ]. In this work, the effect of one-sided biomass-fueled flaming at different intensities (slow and fast speed flaming) on plant community composition and abundance in the vineyard was assessed in comparison to mechanical tillage and mowing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to hot water alone, the addition of foam requires less water, has a lower susceptibility to weather changes, a high application accuracy and speed as well as a low cost (Peerzada and Chauhan, 2018;Wei et al, 2010). The aboveground vegetative tissues of weeds can be effectively controlled by hot water and hot foam (Hansson and Matsson, 2002;Martelloni et al, 2019Martelloni et al, , 2020. In fact, most thermal methods affect the aboveground portion of the plants, however some weeds (i.e., perennial weeds) may regrow from their belowground components (Peerzada and Chauhan, 2018;Kup and Saglam, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The regrowth of weeds after the death of the aboveground vegetative tissues is an important indicator in validating the effectiveness of a weed control technique. Given that a technique should kill the weeds after being applied, the time weeds take to regrow and cover the ground again is an indicator of how many times the technique needs to be repeated in the annual management of weeds (Martelloni et al, 2020). To the best of our knowledge, there has been no research comparing different doses of hot foam and hot water to control weeds.…”
Section: Introductionmentioning
confidence: 99%